STAFF MOTIVATION AS A WAY OF PREVENTING AND RESOLVING LABOR CONFLICTS AT THE ENTERPRISE - LIUBOKHYNETS, Larysa (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of the article is the scientific substantiation of the theoretical-methodical and applied principles of prevention and resolution of labor conflicts at the enterprise through the introduction and improvement of staff motivation, which will take into account both work results and other important conditions for the organization of productive and effective social-labor relations. The article defines the importance of the formation of socio-economic conditions that will provide for the effective settlement of labor conflicts at the enterprise. There are many ways to prevent and resolve labor conflicts, but the success of many leading companies confirms the importance of developing and implementing motivational programs that include various tools for creating a favorable and conflict-free social and labor environment and increasing productivity and work efficiency. Priority has been given to improving staff motivation with the aim of increasing productivity and work efficiency and simultaneously preventing and resolving labor conflicts at the enterprise. At enterprises, labor conflicts are a constant phenomenon, and their prevention and resolution are often a difficult task for management. Forms and sources of personnel motivation in the context of prevention and resolution of labor conflicts at the enterprise are determined. Emphasis is placed on a number of rules and conditions that must be followed when forming a motivational system at the enterprise and solving the task of resolving labor conflicts. The necessity of introducing a structural approach to the organization of the calculation and payment of wages, which at the same time is capable of performing the functions of motivation in ensuring productive and efficient work and regulating social and labor relations with the aim of preventing conflicts among personnel, has been determined.